The effect of soil microplastics on Oryza sativa L. root growth traits under alien plant invasion - Li, Guanlin; Zhao, Xiaoxun; Iqbal, Babar; Zhao, Xin; Liu, Jingjing; Javed, Qaiser; Du, Daolin (Frontiers in Ecology and Evolution, 2023)
Invasive alien plant poses a severe threat to agroecosystems. Meanwhile, microplastic (MP) contamination in the farmland soil is also a cause of concern as they elicit crop stress and reduce productivity. However, it is still being determined how the invasion of alien plants and MP present in the soil impact the crops. Here, belowground plant characteristics associated with stress responses were examined in a pot experiment using root scan analyses of rice plants exposed to S. canadensis invasion, polyethylene MP contamination, and a combined treatment. The observed changes in root growth traits under the Canada goldenrod (Solidago canadensis. L) invasion treatment were the least adverse, whereas S. canadensis invasion combined with soil MP contamination was the most adverse. S. canadensis invasion increased all belowground indices except root height and mean root diameter, which was raised in the soil MP contamination treatment. Combined treatment with S. canadensis invasion and soil MP contamination reduced the belowground root traits more than the other treatments. The alterations in root growth traits may be because of changes in the antioxidant enzyme activity of the root caused by treatments. These insights raise concerns regarding potential yield, economic losses, and the consequences of a possible transport into the food web.